2003
DOI: 10.1046/j.1471-4159.2003.01851.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposite regulation by typical and atypical anti‐psychotics of ERK1/2, CREB and Elk‐1 phosphorylation in mouse dorsal striatum

Abstract: The two mitogen-activated protein kinases (MAPKs), extracellular signal-regulated protein kinase 1 and 2 (ERK1/2), are involved in the control of gene expression via phosphorylation and activation of the transcription factors cyclic AMP response element binding protein (CREB) and Elk-1. Here, we have examined the effect of haloperidol and clozapine, two antipsychotic drugs, and eticlopride, a selective dopamine D 2 receptor antagonist, on the state of phosphorylation of ERK1/2, CREB and Elk-1, in the mouse dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
94
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 40 publications
19
94
2
1
Order By: Relevance
“…PKA-mediated phosphorylation at Thr34 converts DARPP-32 into an inhibitor of PP-1, thereby suppressing the dephosphorylation of numerous effector targets acting downstream of the cAMP/PKA cascade (Greengard, 2001). Haloperidol is known to increase DARPP-32 phosphorylation at Thr34 in vivo (Pozzi et al, 2003). Western blot analysis revealed a significant increase in the levels of phospho-Thr34-DARPP-32, determined in our experimental conditions 15 and 60 min after administration of haloperidol (Figure 7a).…”
Section: Haloperidol-induced Phosphorylation Of Rps6 Depends On Pka-mmentioning
confidence: 60%
See 2 more Smart Citations
“…PKA-mediated phosphorylation at Thr34 converts DARPP-32 into an inhibitor of PP-1, thereby suppressing the dephosphorylation of numerous effector targets acting downstream of the cAMP/PKA cascade (Greengard, 2001). Haloperidol is known to increase DARPP-32 phosphorylation at Thr34 in vivo (Pozzi et al, 2003). Western blot analysis revealed a significant increase in the levels of phospho-Thr34-DARPP-32, determined in our experimental conditions 15 and 60 min after administration of haloperidol (Figure 7a).…”
Section: Haloperidol-induced Phosphorylation Of Rps6 Depends On Pka-mmentioning
confidence: 60%
“…In striatopallidal neurons, blockade of D2Rs increases the state of phosphorylation of several substrates of PKA (Bertran-Gonzalez et al, 2008Håkansson et al, 2006;Li et al, 2004;Pozzi et al, 2003). This effect has been attributed to the removal of the inhibitory tone exerted by D2Rs on adenylyl cyclase, which leads to the accumulation of cAMP and activation of PKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, chlorpromazine and other phenothiazine derivatives are recognized calmodulin antagonists and clozapine has been found to reduce ERK1/2-MAPK (Pozzi et al, 2003;Ratnakar et al, 1995). These kinases may play a role in the mechanism of action of those antipsychotics which inhibit their activity, for example, clozapine, chlorpromazine, but not in the mechanism underlying the action of other drugs which enhance ERK-MAPK or CaMK activity (Ninan et al, 2003;Pozzi et al, 2003;Yang et al, 2004). Moreover, the lack of chlorpromazine and clozapine effect on phospho-Ser-133-CREB level rather excluded their action via this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…335 Already, studies have shown that clozapine and haloperidol induce distinct patterns of phosphorylation of gene expression controlling kinases in the dorsal striatum, indicating a possible explanation for their difference in antipsychotic activity. 339,340 This is an exciting area which will undoubtedly improve our knowledge on determinants of response variability.…”
Section: Epigenetic Factorsmentioning
confidence: 99%